Understanding change and changeability: The ethics of disagreement in Islamic thought - Ali, Md. Yousuf (Journal of Academic Perspectives, 2015)
Disagreement without standard norms and values has become a dangerous trend as a slogan and motto in the contemporary history of human society, particularly in Muslim society. While it has been used by Islamic scholars as a means of developing Islamic thought and bringing positive socio-cultural and economic-political changes, it has been leveled as extremism/terrorism by politicians and civil society for their political interest or power struggle in contemporary time. Examples of disagreement in bringing changes include; the military administration and Ikhwanul Muslimun disagreement in Egypt, Sunni-Shiite disagreement, changes through the democratic process by the Justice party in Turkey, changes through Islamic revolutionary process in Iran, changes through the democratic process by Ikhwan al-Muslimin in Egypt, changes in Islamic moderate approach by al-Nahdah in Tunisia, and changes through the democratic process with moderate approach by Bangladesh Jamat-i- Islami in Bangladesh and Pakistan. Differences of opinion are also found among Muslim exegetes’ interpretation of the Qur`an such as contextual and historical interpretation by feminists, explanatory analysis by rationalists and literal interpretation of the Qur`an by the traditionalists. However, the most dangerous malady that afflicts the Muslim Ummah is that of disagreement and discord that has penetrated into people’s ideas, beliefs, views, opinions, morality, behavior language, and interactions. The early Muslims’ disagreements were not the cause of separating one from another and managed to rid their personal weaknesses. The recent contours of disagreement are related to various groups and organizations. In these situations, the question arises how to bring positive changes through disagreement where people have differences of opinions and views. It is also important for any tradition to have a systematic hermeneutical framework towards an ethics of disagreement for beneficial and meaningful change. In religion, it is not difficult to find a hermeneutical methodology that allows for differences and otherness to live side by side, towards unity in diversity. It only needs to be reviewed. Given the context, there is a need to examine the meaning, brief history, the causes and ethics of disagreement, and to analyze these within the purview of contemporary Islamic thought based on the textual arguments of the Qur`an and Sunnah. This paper also briefly reviews the responses of Muslim scholars with a textual analysis and inductive approach to analyzing the prospects of formulating an Islamic stance on changes and disagreements with ethics in the current context. It is also hoped that the ideas raised will ultimately contribute to understanding and clarify the Islamic stance on the issues for both Muslim and non-Muslim communities in contemporary society.